2019
DOI: 10.1007/s10767-019-09326-7
|View full text |Cite
|
Sign up to set email alerts
|

Duelling Commonwealth Family of Nations Metaphors and Britain’s Post-Brexit Global Identity

Abstract: This study examines the communication of conceptual metaphors in contemporary narratives of British politics, and specifically, the competitive communication of a Commonwealth 'family of nations' metaphor in the context of ongoing Brexit debates. This line of inquiry has been pursued through an analysis of parliamentary speeches made in the House of Commons and the House of Lords in the period from 23 June 2015 (1 year before the EU Referendum) through October 2018, facilitated by the use of computer-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Political scientists have noted the prominent role that conservative historians who support the idea of deepening Anglosphere ties have played in the debate about Brexit (Vucetic, in press). A study of how speakers in parliament represented the Commonwealth in the period between June 2015 and October 2018 (Eaton, 2019) has shown that there was a marked increase in the frequency of references to the Commonwealth as a ‘family of nations’ in the 2-month period following Theresa May’s 17 January 2017 ‘Global Britain’ speech. Eaton (2019) found that Conservative speakers were far more likely to use the metaphor of the Commonwealth as a family than were speakers in other political parties, particularly Labour, with this metaphor being used 59 times by Conservative MPs and just four times by Labour MPs.…”
Section: Introductionmentioning
confidence: 99%
“…Political scientists have noted the prominent role that conservative historians who support the idea of deepening Anglosphere ties have played in the debate about Brexit (Vucetic, in press). A study of how speakers in parliament represented the Commonwealth in the period between June 2015 and October 2018 (Eaton, 2019) has shown that there was a marked increase in the frequency of references to the Commonwealth as a ‘family of nations’ in the 2-month period following Theresa May’s 17 January 2017 ‘Global Britain’ speech. Eaton (2019) found that Conservative speakers were far more likely to use the metaphor of the Commonwealth as a family than were speakers in other political parties, particularly Labour, with this metaphor being used 59 times by Conservative MPs and just four times by Labour MPs.…”
Section: Introductionmentioning
confidence: 99%
“…This metaphor functioned to deepen the political, economic, military, social and cultural ties between Britain and the settler colonies (Bell, 2009;Brysk et al, 2002;McIntyre, 1998;Namusoke, 2016). In the process, a collective identity could be created between the people of Britain and those in the white dominions, strengthening the United Kingdom's position in the international system (Eaton, 2020). An inherent part of this conception was the presentation of Britain as a generous and welcoming 'mother country '. Furthermore, this metaphor is gendered because it is based on a notion of social hierarchy within the unity of the family, where gender functions as a tool of subordination (McClintock, 1993).…”
Section: The Metaphor Of the 'Family'mentioning
confidence: 99%
“…According to Nadine Chan, however, the way this metaphor is used changes depending on what the 'mother country' needs (Chan, 2013). When there is economic or political instability or threat, the family metaphor is used to substitute cooperation with local people for colonial hierarchy (Chan, 2013;Eaton, 2020). The family metaphor was not unique to Britain or the British empire and was used in other contexts too (Buettner, 2017;Laarman, 2013;Mills & Lefrançois, 2018).…”
Section: The Metaphor Of the 'Family'mentioning
confidence: 99%